Training Future Educators with ClassDojo: Enhancing Students' Engagement and Pedagogical Innovation - Cui, Siti Khafifah Shaleh N; Zebua, Muharni Sartika; Harefa, Erlin Harta Yanti; Telaumbanua, Yasminar Amaerita (Bima Abdi: Jurnal Pengabdian Masyarakat, 2025)
This community service activity describes the implementation and outcomes of a workshop-based training on the use of ClassDojo for pre-service teachers at the Faculty of Teacher Training and Education (FKIP), Universitas Nias. The training aimed to develop participants’ digital teaching competence, particularly in classroom management, student engagement, and home-school communication. Ten participants attended the workshop, which combined live demonstrations, hands-on practice, and collaborative discussions. The training covered account creation, classroom setup, behavior management, student portfolios, parent messaging, and classroom analytics. Data were collected through pre- and post-training questionnaires, observation, and participant reflections. Results showed that all participants successfully completed basic features, while completion rates for advanced features such as messaging and analytics ranged from 70% to 80% due to time and connectivity constraints. The workshop effectively improved participants’ confidence and readiness to integrate ClassDojo into their teaching practice, demonstrating that structured, hands-on training can significantly enhance digital literacy among pre-service teachers.